Molecular cytogenetic investigations of synchronous bilateral breast cancer. Issue 9 (27th August 2003) - Agelopoulos, K; Tidow, N; Korsching, E; Voss, R; Hinrichs, B; Brandt, B; Boecker, W; Buerger, H
Abstract : Background: Bilaterality in breast cancer is a rare event and together with an early onset of disease points towards inheritance of the disease. However, most cases seem to occur sporadically, either in a synchronous or metachronous manner. Methods: Thirty two invasive carcinomas and one in situ carcinoma from 16 patients with synchronous, bilateral breast cancer were investigated by means of comparative genomic hybridisation (CGH) and polymerase chain reaction based multiplex microsatellite analysis. The results were analysed conventionally and were also subjected to a biomathematical cluster analysis. Results: On average, bilateral breast cancer cases showed a low number of genetic alterations, a low frequency of genetic amplifications, and a high rate of chromosomal 16q losses. A distinct, characteristic genetic alteration associated with bilateral breast disease could not be found. Although two tumour pairs appeared to be related using biomathematical processing for microsatellite analysis, this result was reproduced by CGH data processing in one patient only. Conclusions: Most synchronous, bilateral breast cancer cases seem to represent independent tumours rather than metastatic events. Nevertheless, the possibility of a specific susceptibility remains.